Determinan Debt to Equity Ratio pada Perusahaan Logam dan Sejenis yang terdaftar di Bursa Efek Indonesia - Dewi Rafiah Pakpahan (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2020)
This study aims to determine the effect of sales growth on Debt to Equity Ratio, determine the effect of return on equity on Debt to Equity Ratio, determine the effect of Firm Size on Debt to Equity Ratio, determine the effect of total assets turnover on Debt to Equity Ratio and to determine the effect of sales growth, return on equity, size and total assets turnover on the Debt to Equity Ratio in Metal and Similar Companies listed on the Indonesia Stock Exchange (IDX). The data collection technique is done by using documentation study technique. The data analysis technique used is multiple linear regression. The results showed that return on equity had a negative and insignificant effect on the Debt to Equity Ratio. Firm Size has a positive and significant effect on the Debt to Equity Ratio. Total asset turnover has a positive and significant effect on Debt to Equity Ratio. And simultaneously Sales growth, Return On Equity, Firm Size and Total Asset Turnover have a significant effect on Debt to Equity Ratio in Metal and Similar Companies listed on the Indonesia Stock Exchange in 2014 – 2018